A pair of bubbles' rising dynamics in a xanthan gum solution: a CFD study. Issue 11 (7th February 2015) - Islam, Md. Tariqul; Ganesan, P.; Cheng, Ji
<x xml:space="preserve">Abstract</x> The motion and interaction of a bubble pair in a non-Newtonian fluid are numerically simulated by a volume of fluid method. The effects of initial horizontal bubble interval, oblique alignment and fluid rheological properties on the pair of rising bubbles are evaluated.